Critical Thinking in Higher Education and Labour Market - Indrašienė, Valdonė (Erziehungskonzeptionen und Praxis, 2021)
This book presents the comprehensive investigation of critical thinking in higher education from the perspectives of the study and labor market. It looks for an answer to the vibrant question of what and to whom critical thinking is. The study brings together findings from systematic literature review, analysis of descriptions of higher education study programs and study subjects, phenomenographical research and survey and supplements the existing perceptions of critical thinking with novel data-driven insights. The book reveals how critical thinking manifests itself in the contexts of higher education and the labor market and advocates for the significance of the critical thinking at personal, interpersonal, and social levels.